Pathological crying induced by deep brain stimulation of the subthalamic nucleus in Parkinson’s disease - Wolf, Marc; Blahak, Christian (Journal of clinical neuroscience, 2017)
We report on a patient with deep brain stimulation (DBS) of the subthalamic nucleus (STN) for Parkinson’s disease (PD) who developed pathologic crying (PC) immediately postoperatively. A spread of DBS current to adjacent cortico-ponto-cerebellar pathways might be responsible. In contrast to the few cases published previously, there was no pre-existing additional lesion that would have favoured occurrence of PC. Treating physicians should be aware of DBS-induced PC.
Gesehen am 16.08.2018